ANATOMICAL EXPLANATION OF ABSORPTION OF SNEHA DRAVYA IN SIROBASTI KARMA - Jayantkumar, *Shrimali Dipakkumar; Bhatnagar, Vikash (AYUSHDHARA, 2016)
Ancient scholars of Ayurveda have described head as a root of the body and explained the diseases related to Sira. According to Aacharya Sushruta in this region there are 37 Marmas (vital points), which indicate its importance. For the diseases of Sira many treatment modalities are explained like, Sirobasti, Sirodhara, Siroabhayang, Pichu and Nasya. Among them Sirobasti Karma is very effective in mental disorders and many scalp related problems but its mode of action and the route of oil absorption is not clearly explained in classics. The route for oil absorption can be explained scientifically by the knowledge of anatomy of scalp. The scalp is made up of five layers: skin, superficial fascia, aponeurosis, loose areolar tissue and pericranium. The oil used in Sirobasti is absorbed transversally into the scalp through the skin. The connective tissue layer of scalp is rich in blood vessels and nerves. In the loose areolar tissue of scalp, emissary veins are present, these veins are valve less and connects the superficial veins of the scalp with the diploic veins of the skull bones which drains into the intracranial sinuses. By the knowledge of this venous drainage system of Scalp we can explains the systemic effects of Shirobasti therapy thus Sirobasti therapy can be used effectively for various scalp related problems and mental disorders.